BizTalk Server 2004 in an investment bank the agile service-oriented architecture becomes a reality. - Regan, David
This article describes recent work in a leading investment bank using Microsoft's BizTalk Server 2004 (BizTalk) as an integral component of a service-oriented architecture. I'll describe how BizTalk is used to implement lightweight workflow that builds new services from existing services and ties in tactical solutions to enable straight through processing (STP) of service requests.